Effects of commercial enrichment diets on the nutritional value of the rotifer (Brachionus plicatilis) - Fernández-Reiriz, María José; Labarta, Uxío; Ferreiro, M. J. (Aquaculture, 1993)
12 páginas, 4 tablas The rotifer, Brachionusplicatifis, pre-fed on baker’s yeast, was enriched for 6 h with three commercial products from Artemia Systems S.A., namely Protein Selco (microcapsules), Dry Selco (microparticles) and Super Selco (an emulsion containing high levels of n-3 HUFA). The biochemical composition (protein, carbohydrate, total lipid, lipid classes and fatty acids) and dry weight ofthe rotifers before and after the enrichment experiments were studied. Two of the enrichers, Dry Selco and Super Selco, are rich in lipid but poor in protein and carbohydrate. Protein Selco contains lipid as well as protein and carbohydrate. The biochemical composition and the dry weight of the rotifers were changed after 6 h of enrichment. The percentage of protein and lipid increased with all of the three enrichers and the percentage of carbohydrate decreased slightly. Rotifer dry weight increased in rotifers enriched on Protein Selco. Phospholipids, sterol esters+ waxes, triacylglycerols and free fatty acids increased after the enrichment with the three enrichers while sterols slightly decreased when the rotifers were fed on Protein Selco. The fatty acid content of the rotifers increased after the enrichment with all ofthe enrichers and this increase was particularly apparent in the case of n-3 HUFAs (20: Sn-3 and 22 : 6n-3). This work was supported by the contract-project “ Larval Nutrition of Turbot” with the fish farm Cultivo de Peces S.A. (CULTIPECSA). Peer reviewed